Tingkat Pengetahuan Dan Kepatuhan Tentang DIIT Diabetes Mellitus Pada Pasien Diabetes Mellitus Di Puskesmas Sibela Kota Surakarta - Insiyah Insiyah; Rini Tri Hastuti (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Knowledge, Compliance, Diabetes Mellitus Diet. The purpose of this study was to identify knowledge and compliance to type 2 diabetes diet in diabetic patients in Sibela Public Health Centre Surakarta. Result of this research will be utilized for a health education program for type 2 diabetic patients in the community. Sample of this research is type 2 diabetic patients by using purposive and snowball sampling. This research also includes health professional such as a physician, nutritionist, and senior nurses for data triangulation. The instrument in this research are a netbook, tape recorder, and semi-structured questionnaire to record the data from a deep interview. The results show that there are various knowledge and compliance with a diabetes diet in diabetic patients in Sibela Public Health Centre Surakarta. Patients have incomplete knowledge about diabetes mellitus. Patients are already well known about signs and symptoms, etiology, treatment, and diabetic complication but they are still uncertain with the number of energy needed and have no diet planning. Diet compliance is still low and patients consume more carbohydrate(>65%) as a source of energy. This lack of compliance can be influenced by the low of knowledge that can be resulted from the lack of information and the low of the level of education and motivation. Refreshing of diabetes diet, family support and motivation from health professional through effective communication among health professional and family, monitoring nutritional status and appropriate diet is very important.